HIGH-SENSITIVITY C-REACTIVE PROTEIN IN THE FIRST TRIMESTER OF PREGNANCY IN OBESE PATIENTS WITH GESTATIONAL DIABETES - Belomestnov Sergey Razumovich; Сhumarnaya Tatyana Vladislavovna; Sevostyanova Olga Yurievna; Ksenofontov Aleksey Mikhaylovich; Isakova Tatyana Mikhaylovna; Prazdnichkova Ekaterina Dmitrievna (Паёми Сино)
Objective: To determine the prognostic value of high-sensitivity C-reactive protein (hsCRP) levels in the first trimester for the risk of gestational diabetes mellitus (GDM) in obese pregnant women. Methods: A prospective observational descriptive cohort study included 105 obese women with a body mass index (BMI) ranging from 25.0 to 29.99 kg/m² in the first trimester. The main group consisted of 31 pregnant patients with GDM. The control group included 74 pregnant women without carbohydrate metabolism disorders. BMI and hsCRP concentration in venous blood serum were determined for each woman. All laboratory measurements were performed simultaneously in the same laboratory by the same specialist. The median, 1st, and 3rd quartiles were used to describe the central tendency. The diagnostic value of the parameters (GDM prognosis) was assessed using the area (AUC) under the characteristic receiveroperating curve (ROC). Differences were considered statistically significant if p<0.05. Results: A statistically significant increase in the hsCRP concentration was found: 2.5 [0.4; 5.35] mg/l in the main group compared to the 0.4 [0.4; 0.4] mg/l in the control group (p<0.001). The value of hsCRP for GDM prognosis was confirmed: AUC=0.77 (p<0.001), and the cut-off threshold was 0.5 g/ ml (sensitivity=68%, specificity=85%).Conclusion: The study's findings suggest that an hsCRP concentration above 0.5 mg/l could be a valuable screening tool for obese pregnant women with normal glycemic levels in the first trimester. This marker could serve as an additional prognostic criterion for GDM, equipping healthcare professionals with a powerful tool for early risk identification.